(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Flight delay is a challenging problem in the aviation industry, as it can cause significant costs for airlines, operators, and travelers. Machine learning methods have been applied in various studies to predict flight delay, but relying only on a single route or airport may not be sufficient to forecast the future of flights.